Plasma lacosamide monitoring in children with epilepsy: Focus on reference therapeutic range and influencing factors - Li, Yue; Guo, Hong-Li; Zhang, Yuan-Yuan; Dong, Na; Hu, Ya-Hui; chen, Jing; Lu, Xiao-Peng; Chen, Feng (Frontiers in Pediatrics, 2022)
Background: Lacosamide (LCM) is a newer anti-seizure medication (ASM) that was approved in China in 2018, but its real-world clinical data and plasma concentrations in Chinese children with epilepsy are very limited. Of note, the reference range for routine LCM therapeutic drug monitoring (TDM) is still unknown. The purpose of this study was to investigate the efficacy and safety of LCM and to evaluate the potential factors affecting its efficacy and variable LCM plasma concentrations in Chinese children with epilepsy. Methods: Children with epilepsy (< 18 years) with routine plasma LCM monitoring from March 2019 to December 2021 at the Department of Pharmacy, Children's Hospital of Nanjing Medical University were retrospectively collected. Results: 76 pediatric patients (52 males) were finally enrolled. Mean age was 7.9 years with a mean dose of LCM 6.3 mg/kg/d. The TDM data as a whole showed that the median plasma trough concentration (C0) was 3.42 μg/mL. A 6-month LCM add-on therapy produced 70% of patients achieving ≥50% seizure frequency reductions, Interestingly, more patients who took LCM monotherapy achieved seizure freedom over the same periods of follow-up observations. Under maintenance dosages, approximately 92.1% of the C0 values were 2.0–7.0 μg/mL. The plasma-C0-to-daily dose (C0/Dose) ratio was significantly associated with age and body weight (BW). The C0/Dose ratio in patients aged 1–≤6 and 6–≤12 years was significantly higher by 81% and 29% than those aged 12–≤18 years, respectively. The C0/Dose ratio in patients with a BW of ≥40 kg was 1.7-fold lower than in patients with a BW of ≤20 kg. In addition, complex LCM-ASMs interactions were observed. Oxcarbazepine (OXC) significantly decreased the C0/Dose ratio of LCM. Conclusion: This retrospective study confirmed the effectiveness and tolerability of the LCM treatment in children with focal epilepsy. Children with higher BW and older age have lower C0/Dose ratios. Complex drug interactions between LCM and other concomitant ASMs were revealed. Notably, based on the data in our hands, the reference range, i.e., 2.0–7.0 μg/mL, for routine LCM monitoring may be feasible. The real-world evidence of this study supports LCM as a promising option in children with focal epilepsy.